2007
DOI: 10.1002/jmri.20888
|View full text |Cite
|
Sign up to set email alerts
|

Assessing normal pulse wave velocity in the proximal pulmonary arteries using transit time: A feasibility, repeatability, and observer reproducibility study by cardiovascular magnetic resonance

Abstract: Purpose: To calculate pulse wave velocity (PWV) in the proximal pulmonary arteries (PAs) by cardiovascular magnetic resonance (CMR) using the transit-time method, and address respiratory variation, repeatability, and observer reproducibility.Materials and Methods: A 1.9-msec interleaved phase velocity sequence was repeated three times consecutively in 10 normal subjects. Pulse wave (PW) arrival times (ATs) were determined for the main and branch PAs. The PWV was calculated by dividing the path length traveled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…For PWV estimation, typically transit-time methods are employed estimating temporal differences of specific features of blood flow waveforms, e.g., time from foot to foot or peak to peak, between two locations of the vessel with known distance (11-24). However, the precision of this method highly depends on the exact calculation of flow difference and distance between only two measuring points (16,25,26).Methodological improvements include a more continuous evaluation along a vessel center line and cross-correlation (XCor) analysis for the estimation of waveform delays, which improved the accuracy of PWV estimation but relied on 2D PC acquisitions in sagittal oblique slices exactly transecting the thoracic aorta (27,28). Recently, more comprehensive three-dimensional (3D) CINE techniques in combination with three-directionally encoded velocities (flow-sensitive four-dimensional [4D] MRI) have been reported that provide information on multidirectional in vivo blood flow with full volumetric coverage of the vessel of interest (29)(30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For PWV estimation, typically transit-time methods are employed estimating temporal differences of specific features of blood flow waveforms, e.g., time from foot to foot or peak to peak, between two locations of the vessel with known distance (11-24). However, the precision of this method highly depends on the exact calculation of flow difference and distance between only two measuring points (16,25,26).Methodological improvements include a more continuous evaluation along a vessel center line and cross-correlation (XCor) analysis for the estimation of waveform delays, which improved the accuracy of PWV estimation but relied on 2D PC acquisitions in sagittal oblique slices exactly transecting the thoracic aorta (27,28). Recently, more comprehensive three-dimensional (3D) CINE techniques in combination with three-directionally encoded velocities (flow-sensitive four-dimensional [4D] MRI) have been reported that provide information on multidirectional in vivo blood flow with full volumetric coverage of the vessel of interest (29)(30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…For PWV estimation, typically transit-time methods are employed estimating temporal differences of specific features of blood flow waveforms, e.g., time from foot to foot or peak to peak, between two locations of the vessel with known distance (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). However, the precision of this method highly depends on the exact calculation of flow difference and distance between only two measuring points (16,25,26).…”
mentioning
confidence: 99%
“…PWV has been studied as a noninvasive measure of PA stiffness 8, 29, 30, 31. A major difficulty in measuring PWV is related to the change in the shape of pressure and flow waves with distance that makes it difficult to assign a single value that is definitive for the entire wave.…”
Section: Discussionmentioning
confidence: 99%
“…Application of PWV to PA is further complicated by PA anatomical features because of its short distance and curvature, and a need for a high temporal resolution CMR 32. Except studies measuring PWV in normal subjects,30, 31 other studies involving PWV and analysis of RV CMR indexes were performed in patients with advanced PAH with overall much higher values of mean pulmonary artery pressure and PVR, thus limiting its clinical use 8, 29, 33, 34. The latter is also true for studies applying the dynamic contrast–enhanced magnetic resonance imaging in pulmonary vascular system in patients with advanced PAH 35, 36.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, application of the flow-area method (18) allows PWV estimation from a single phase contrast slice. Repeatability of 2D phase-contrast-derived PWV values in the proximal pulmonary arteries was assessed using a transit time algorithm by Bradlow et al (19). On a smaller cohort of healthy volunteers, Rogers et al found no statistically significant differences in PWV values from 2D phase contrast when two consecutive acquisitions based on different localizers were performed, and after removing and repositioning the subject in the scanner (20).…”
mentioning
confidence: 99%